Analisis Sistem Pelaporan Keuangan dalam Pengelolaan Dana Infaq dan Shadaqah - Anggraini, Reni Dwi Nur; Prastyaji, Arif Nur; Gusra, Rakha Aiman; Damayanti, Risca Evi (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2022)
This study aims to analyze the financial reporting system impacts the management of Infaq and Shadaqah funds. The method used in this research is literature study, which is one method of collecting library data, reading and taking notes, and processing research materials. The journals under study are journals from 2015–2021. This research is addressed to the Infaq and Sadaqah Management Institute, which has been registered and has received permission from the government. Based on the results of the analysis, two of the four journals studied have implemented a financial reporting system based on PSAK 109. While the other two have not implemented PSAK 109, the factor that causes this is that the Amil Zakat Institution separates the Statement of Changes Fund and presentation in different financial statements. Keywords: Financial Statements, Infaq, Sadaqah.